PERAN BAURAN PEMASARAN PENDIDIKAN ISLAM DALAM MENINGKATKAN CITRA DAN KUALITAS LEMBAGA PENDIDIKAN ISLAM - Miftahul Huda; Sidiq Purnomo (CV. ADIBA AISHA AMIRA, 2025)
The main objective of this study is to analyse the role of Islamic education marketing mix in improving the image and quality of educational institutions. This research aims to explore and understand how the elements of the marketing mix (product, price, place, and promotion) can be integrated effectively in the context of Islamic education, as well as its impact on public perception and the quality of education in the institution. This research uses a qualitative method with a case study approach at NU Al Islami Pesanggaran Junior High School to analyse the application of the marketing mix based on Islamic values. Data were obtained through interviews, observation, and document analysis, then analysed thematically. Triangulation and member checking were used to ensure the validity of the data, resulting in an in-depth understanding of the school's marketing strategy.The main conclusion of this study is that NU Al Islami Pesanggaran Junior High School successfully implemented an Islamic values-based marketing mix, utilised effective promotional strategies, and provided quality facilities. This integration enhances the school's image, builds parental trust, and makes it the top choice for people who want a moral and spiritual-based education.